Study on Runoff and Climate Change Response of Upper and Middle Reaches of Xiuhe River Basin Based on SWAT Model - HUANG Yipeng; LIU Weilin; WAN Yifan; WEN Hongan; WU Bin; LIU Lina; ZHU Shengnan (Renmin Zhujiang)
Study on distributed hydrological simulation,model parameter sensitivity analysis and response of climate change to runoff are of important practical significance and scientific value for control of flood and drought disasters and distribution of water resources in the Xiuhe River Basin.Taking the upper and middle reaches of Xiuhe River Basin as research area,this paper builds the SWAT localization model to simulate runoff,and conducts the quantitative analysis on the response of runoff of Xiuhe River Basin to climate change with 55 climate scenarios (temperature increases or decreases 0~2℃,precipitation increases 0~60% or decreases 0~40%,respectively) as input of SWAT model.Results show that:In calibration period,the correlation coefficient R2 is 0.87,and the Nash coefficient Ens is 0.86,while,0.87 and 0.83 respectively in verification period,proving the high applicability of SWAT model in runoff simulation of Xiu River Basin;10% change of precipitation in Xiuhe River Basin has an impact on its runoff of 8.9%~10.7%;1℃ change of temperature has an impact on its runoff of only 0.3%~1.3%;precipitation is the main influencing factor of runoff change;after analyzing the climate scenario grid,when the precipitation is between -40% and +50%,the precipitation-temperature-runoff is basically linearly correlated,which can be presented by a plane function.In extreme precipitation cases,the relationship between temperature and runoff is nonlinear.